PEMBERDAYAAN PETANI MELALUI PERAN KELOMPOK TANI PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA - Wa Ode Santi; Awaluddin Hamzah; Yoenita Jayadisastra (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
Farmer empowerment is expected to have an impact on increasing the role of wet-rice farmer groups, thereby encouraging the welfare of farmers and their families. The objective of this study is to ascertain the extent of farmer empowerment and the role of paddy rice farmer groups in Baruga Subdistrict, as well as to examine the relationship between the two. The study population consisted of all wet-rice farmers (N = 197) who were members of 13 wet-rice farmer groups. The sample size was calculated using the Slovin formula with an error rate of 15%, resulting in a sample size of 30 respondents for the study. Data were collected through observation, interviews, and document analysis with the assistance of questionnaires, which were administered via the media. The variables under investigation in this study are farmer empowerment and the role of farmer groups. The data were analyzed descriptively and quantitatively using the interval formula and the Spearman rank correlation formula. The results demonstrated that the empowerment of wet-rice farmers in Baruga Subdistrict has been effectively implemented. This is evidenced by the elevated levels of awareness and aspiration, the enhanced capacity to overcome challenges, and the elevated levels of ability to collaborate in farmer empowerment activities. The role of farmer groups in paddy rice farming has been fulfilled effectively, as evidenced by the fulfillment of each role of farmer groups, namely the role as a vehicle for learning, a vehicle for cooperation, and a production unit. The relationship between farmer empowerment and the role of paddy rice farmer groups is statistically significant, with a correlation coefficient value of 0.007. This indicates that as farmer empowerment improves, the role of paddy rice farmer groups in Baruga Village also improves.